The contact erosion characteristics of SF6 circuit breaker based on dynamic resistance measurement method. (November 2022) - Chen, Gong; Li, Mengbo; Wang, Qi; Lu, Xiaojun; Zhang, Sixiang; Luo, Daijun
Abstract: For the purpose of investigating the contact erosion characteristics in breaking process of SF6 breaker, an erosion experiment was conducted on the tested SF6 circuit breaker. As a result, the relationship between the dynamic resistance and contact travel in various levels of degradation was acquired. The SF6 contact state parameters were obtained from the experimental results. Considering the parameters change, the follow-up conclusions can be sum up: (1) The contact travel's minimum value is deduced to be 14.2 mm; (2) The numerical value of contact resistance has an acceptable range, which is 50 ∼ 150 μ Ω for main contact and 200 ∼ 400 μ Ω for arcing contact, respectively. (3) The measured value of arcing contact attenuate length is 0.318 mm, which remains unchanged in each erosion test. Taking all the mentioned above into consideration, we research on the contact material erosion process during the opening operation and the effect on the circuit breaker property. In the meantime, the theoretical calculation formula of length decrement in arcing contact is deduced. Based on the formula, the calculated value is 0.268 mm for each trial, which is close to the measured value of 0.318 mm. At last, the prediction methods for the SF6 circuit breaker's electrical life is summarized.